2017
DOI: 10.1080/21580103.2017.1355335
|View full text |Cite
|
Sign up to set email alerts
|

Measuring social capital in Indonesian community forest management

Abstract: Social capital provides an overview of a community's togetherness, unity, and mutual trust in achieving common goals towards sustainable development. Community forest management requires a certain level of social capital for sustainable forest management. This study aims to identify and analyze key factors influencing the community's social capital in forest management. The key factors influencing the level of social capital in a community include internal factors such as individual characteristics and knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
2
14
0
3
Order By: Relevance
“…All participants in the FGDs expressed how working together is a tradition within their communities. Other studies support our findings, demonstrating that rural Javanese communities participating in natural resource management have high levels of social capital (Lee et al 2017).…”
Section: Pes and Nonpes Participant Social Capitalsupporting
confidence: 89%
“…All participants in the FGDs expressed how working together is a tradition within their communities. Other studies support our findings, demonstrating that rural Javanese communities participating in natural resource management have high levels of social capital (Lee et al 2017).…”
Section: Pes and Nonpes Participant Social Capitalsupporting
confidence: 89%
“…This indirectly becomes an investment in cultivating trust to prevent negative prejudices among parties during the consensus. It confirmed studies performed by Witasari (2016) and Lee et al (2017) who also assert that trust establishes mutual support for collective action in forest management. Conversely, it may be indicated that the stakeholders' communication in some of consensus projects of previous works such as Margerum (2002) and Poitras et al (2003) is abruptly started in the initial dialogues led to the lack of trust among parties during the process.…”
Section: Process-related Aspectsupporting
confidence: 84%
“…These techniques included interviews with respondents and key persons and focus group discussion. Interviews were conducted with 50 farmers randomly selected from 98 KTHKm members to explore the social capital in the form of motivation (Lee et al 2017). Interviews were also conducted with 7 current formal elite figures in KTHKm, covering the advisor, the two chairpersons, the treasurer, the chief of production facilities, and as well as the chairperson and the treasurer of cooperation section.…”
Section: Data Collectionmentioning
confidence: 99%